De la literatura latinoamericana a la literatura (latinoamericana) mundial Condiciones materiales, procesos y actores - Locane, Jorge J. (Berlin/Boston De Gruyter, 2019)
What is World Literature? To answer this question, this book asks another one: How is it produced, that is, what are the material conditions, processes, and actors, which enable Latin-American Literature to circulate internationally and become (Latin-American) World Literature? Exploring the tension between literature for and of the world, the volume also intend to give visibility$1 (Band value as World Literature$1 (Bto local forms of expression.s
Spanish; Castilian
Keywords: Literature: history & criticism; Literary studies: from c 1900 -; Anagrama; Editorial Policies; World Literature; Literary Market